Conventional Low Intensity Pulsed-Ultrasound Therapy Increases Osteoblast, Serum Alkaline Phosphatase, and Serum Calcium Levels in Fracture Healing Process - Indrayuni Lukitra Wardhani; I Ketut Gede Agus Budi Wirawan; I Putu Alit Pawana; Andriati; Patricia Maria (Cermin Dunia Kedokteran, 2018)
Introduction: Application of ultrasound waves to improve bone healing generally use specific bone stimulator equipment not available in Indonesia. Frequency and duration of therapy from previous studies are very difficult to apply in clinical practice. This study aims to observe the therapeutic effect of conventional low-intensity pulsed-ultrasound to osteoblast, alkaline phosphatase, and serum calcium levels. Method: Thirty six male white rats were divided into three groups (control, USD 5x/week, and USD 3x/week). Tibial fracture in ultrasound groups were treated 3x/week and 5x/week with ultrasound waves (1 MHz, pulsed mode, 20% of duty cycle, intensity of 0.2 W/cm2, duration 10 minutes, stationary) for 3 weeks. Callus tissue and blood from all animals were assessed quantitatively using histological and biochemical analyses. Result: Significant differences (p<0.05) in the average number of osteoblasts, level of alkaline phosphatase, and serum calcium among all three groups. Conclusion: Conventional low intensity pulsed-ultrasound either 5x/week or 3x/week improve bone healing process.   Pendahuluan: Penggunaan gelombang ultrasonik untuk memperbaiki penyembuhan tulang umumnya menggunakan alat stimulasi khusus yang tidak tersedia di Indonesia. Frekuensi dan durasi terapi penelitian sebelumnya sulit diterapkan dalam praktik klinis. Tujuan penelitian ini adalah untuk membandingkan efek stimulasi gelombang ultrasonik menggunakan alat terapi konvensional ultrasound diathermy (USD) antara kelompok kontrol, kelompok perlakuan USD 5x/minggu dan 3x/minggu terhadap jumlah osteoblas, kadar alkali fosfatase, dan kalsium serum. Metode: Sejumlah 36 ekor tikus putih jantan dibagi tiga kelompok (kontrol, USD 5x/minggu, dan USD 3x/minggu). Fraktur tibia pada kelompok ultrasound diterapi 3x/minggu dan 5x/minggu dengan gelombang ultrasonik (1 MHz, pulsed-mode, 20% duty cycle, intensitas 0,2 W/cm2, durasi 10 menit, stasioner) selama 3 minggu. Jaringan kalus dan darah semua hewan dinilai secara kuantitatif dengan analisis histologi dan biokimia. Hasil: Ada perbedaan signifikan (p <0,05) jumlah rata-rata osteoblas, kadar alkali fosfatase, dan kalsium serum antara ketiga kelompok. Simpulan: Terapi konvensional dengan pulsed-ultrasound intensitas rendah frekuensi 5x/minggu ataupun 3x/minggu memperbaiki proses penyembuhan tulang.